Engineering MoS2 nanosheets on spindle-like α-Fe2O3 as high-performance core–shell pseudocapacitive anodes for fiber-shaped aqueous lithium-ion capacitors - Man, Ping (2021)
Fiber-shaped aqueous lithium-ion capacitors (FALICs) featured with high energy and power densities together with outstanding safety characteristics are emerging as promising electrochemical energy-storage devices for future portable and wearable electronics. However, the lack of high-capacitance fibrous anodes is a major bottleneck to achieve high performance FALICs. Here, hierarchical MoS2@α-Fe2O3 core–shell heterostructures consisting of spindle-shaped α-Fe2O3 cores and MoS2 nanosheet shells on a carbon nanotube fiber (CNTF) are successfully fabricated. Originating from the unique core/shell architecture and prominent synergetic effects for multi-components, the resulting MoS2@α-Fe2O3/CNTF anode delivers a remarkable specific capacitance of 2077.5 mF cm−2 (554.0 F cm−3) at 2 mA cm−2, substantially outperforming most of the previously reported fibrous anode materials. Further density functional theory calculations reveal that the MoS2@α-Fe2O3 nano-heterostructure possesses better electrical conductivity and stronger adsorption energy of Li+ than those of the individual MoS2 and α-Fe2O3. By paring with the self-standing LiCoO2/CNTF battery-type cathode, a prototype quasi-solid-state FALIC with a maximum operating voltage of 2.0 V is constructed, achieving impressive specific capacitance (253.1 mF cm−2) and admirable energy density (39.6 mWh cm−3). Additionally, the newly developed FALICs can be woven into the flexible textile to power wearable electronics. This work presents a novel effective strategy to design high-performance anode materials for next-generation wearable ALICs.